Ferritic phase transformation to improve creep properties of martensitic high Cr steels. (September 2016) - Plesiutschnig, Ernst; Beal, Coline; Sommitsch, Christof; Paul, Stefan; Zeiler, Günter
Abstract: Creep properties of two 9% Cr steels, heat treated based on a quenching and partitioning concept are investigated. Austenite is partly transformed into martensite during interrupted quenching. Due to the new interfaces and the deformed retained austenite, it is possible to transform the retained austenite into ferrite and precipitates during subsequent tempering. The kinetics of this transformation is described by the Kolgomorov-Johnson-Mehl-Avrami equation. Creep rupture times are improved by more than 50% compared to conventional heat treated samples. It is expected that this heat treatment improves the creep properties of the entire class of 8–13% Cr steels. Graphical abstract: